Radioluminescence characterization of in situ x-ray nanodosimeters: Potential real-time monitors and modulators of external beam radiation therapy - Souris, Jeffrey S. (Appl Phys Lett, 2014)
Europium-doped yttrium oxide (Y(2)O(3):Eu) has garnered considerable interest recently for its use as a highly efficient, red phosphor in a variety of lighting applications that include fluorescent lamps, plasma, and field emission display panels, light emitting diodes (LEDs), and lasers. In the present work, we describe the development of Y(2)O(3):Eu nanoparticles for a very different application: in situ, in vivo x-ray dosimetry. Spectroscopic analyses of these nanoparticles during x-ray irradiation reveal surprisingly bright and stable radioluminescence at near-infrared wavelengths, with markedly linear response to changes in x-ray flux and energy. Monte Carlo modeling of incident flux and broadband, wide-field imaging of mouse phantoms bearing both Y(2)O(3):Eu nanoparticles and calibrated LEDs of similar spectral emission demonstrated significant transmission of radioluminescence, in agreement with spectroscopic studies; with approximately 15 visible photons being generated for every x-ray photon incident. Unlike the dosimeters currently employed in clinical practice, these nanodosimeters can sample both dose and dose rate rapidly enough as to provide real-time feedback for x-ray based external beam radiotherapy (EBRT). The technique's use of remote sensing and absence of supporting structures enable perturbation-free dosing of the targeted region and complete sampling from any direction. With the conjugation of pathology-targeting ligands onto their surfaces, these nanodosimeters offer a potential paradigm shift in the real-time monitoring and modulation of delivered dose in the EBRT of cancer in situ.